ANALISIS PEMENUHAN KONSEP CURRENT PAYMENT DAN FINAL LIABILITY DALAM PENGHITUNGAN PPH PASAL 25 DAN PENGENAAN SANKSI TERKAIT - Setiabudi, Andang Wirawan (Jurnal Akuntansi, 2019)
Nowadays about 80% of APBN (National Budget) revenue is rooted from tax revenue.  Therefore, Directorate General of Tax Department (Dirjen Pajak/DJP) as the organizer of tax revenue should straighten themselves up constantly in order that they could reach the revenue target which is burdened. One of the actions is through tax reform system which relies on self-assessment system.  People, in this system, are the most in determining of the activity that they should do by themselves connected to the tax; starting from the registration of tax obligatory, counting the amount of owed tax that they have to pay, pay the tax by themselves to the bank or post office and report it to KPP (tax service office). Tax revenue is achieved, among others, from the tax payment and also imposition payment if the tax obligatory has broken the certainty of taxation regulations.  One of them is income tax section 25 payment; it is tax payment on fiscal year in accordance with current payment concept. Each month the payment of PPh section 25 is counted based on PPh of SPT a year before then minus tax credit and divided in 12, in other words; based on the last year benefit which is not reflecting the actual condition of tax obligatory (fictive stelsel), and in the end of the year; it will give the influence in the owed tax. Moreover, this is added by imposition of doubt in case of PPh section 25 that unpaid or minus in payment in the form of interest on 2%  each month on PPh section 25 that unpaid or minus payment.  Those two things about is not in accordance with final liability concept which states that the obligation for income tax would become owed tax in the end of the year.  In addition the doubt would be imposed if the actual income has been known.  In the fiscal year, actuality, the tax obligatory does not owe in Income Tax yet.  So it is not precisely if the Directorate General of Tax department impose a doubt in the form of interest (written on Letter of Tax Claim/Surat Tagihan Pajak/STP) on the PPh payment in fiscal year (PPh 25).  However in the fact, the STP of PPh 25 which unpaid or minus in payment is still brought up continually.